Chemical characterization of the main bioactive polyphenols from the roots of Morus australis (mulberry). Issue 10 (7th October 2019) - Guo, Sen; Liu, Li; Zhang, Shanshan; Yang, Chuang; Yue, Wenping; Zhao, Haoan; Ho, Chi-Tang; Du, Junfeng; Zhang, Hai; Bai, Naisheng
Abstract : Polyphenols from mulberry roots possess antitumor activity and α-glucosidase, acetylcholinesterase and tyrosinase inhibitory activities. Abstract : Morus species, commonly known as mulberry, is widely distributed in China. The mulberry tree is a high-value plant in agriculture. Morus australis is one of the major Morus species growing in Northern China. However, the biological properties of the main constituents of M. australis roots were not well studied. In the present study, through extensive chromatographic and spectral analysis, 12 phenolic compounds were isolated and identified from the M. australis roots. Compounds 1, 2, 8, 9 and 12 were isolated from M. australis roots for the first time. Antitumor activities of these polyphenols were studied on the A549 cell line. Compounds 1, 5 and 6 exhibited cytotoxicity on A549 cells and induced apoptosis in A549 cells via the intrinsic mitochondrial pathway. They also mediated inhibition of autophagic flux contributed cell death via the PI3k/Akt/mTOR pathway. In order to explore more potential bioactivities of these isolates, α-glucosidase, acetylcholinesterase and tyrosinase inhibitory activities were studied, and the results demonstrated that the inhibitory activity of these polyphenols on enzymes was not defined by their basic structural skeletons, but by the substituted position.